Draft Annual Plan 1990-91 Volume IV Government of Assam - Planning Commission (Planning Commission, 1989)
Due to its Geographical location in the N.E. Region, the State of Assam has to serve the purpose of gateway to other neighboring States in the region. Rail Communication system being grossly inadequate, roads have to play a vital role not only as supplementing system but as a parallel means to full-fill the transport needs Accelerated development of Road networks in the State of Assam is of imperative necessity for the Socio-economic regeneration not only for Assam but for the whole of N.E. Region. Considering the importance and urgency of the matter Planning Commission had earlier setup a Working Group for preparation of an integrated Master Plan for road development in the N.E. Region, This Master Plan has been finalized and keeping in view the needs as projected in the Master Plan, physical targets and financial outlays projected in the said Master Plan, the present draft Annual Plan has been framed.
Government of Assam
Planning and Development Department
Keywords: Agriculture & Allied Activities; Rural Development; Special Areas Programmes; Irrigation And Flood Control; Energy Industry & Minerals; Assam Road Transport Corporation; Commissioner of Transport; Transport Survey Cell; Inland Water Transport; Communication Telecommunication System; Science; Technology and Environment; Prevention and Control of Pollution; Other General Economic Services